(3QSGdI JhHjN GdNGFH GdYGLR Sjcjfs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUd cJGH GdTjN GdaGVd hGdLeGYI CjOge Gddg Ydi WGYJg hdi GdOjf hcaGge GdONhd ajeG ESJMSfJg jghO gPg GdCeI s
(3BNQgG (B:s
(3aEfeG JZGdWhf CfaSce hJXdehgG hbO CYPQ ef CfPQ heG Ydi GdQShd GdfGUM Shi GdHdGZ GdeHjf hGdMeO ddg hMOg hHg CSJYjf Je JhHjN GdNGFH hGdMeO dehdGfG hMOg hGdTcQ dhdjg YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B77s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis